2009
DOI: 10.1016/j.freeradbiomed.2009.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Isolevuglandins covalently modify phosphatidylethanolamines in vivo: Detection and quantitative analysis of hydroxylactam adducts

Abstract: Levuglandins (LGs) and isolevuglandins (isoLGs, also called "isoketals" or "isoKs") are extraordinarily reactive products of cyclooxygenase and free radical-induced oxidation of arachidonates. We now report the detection in vivo and quantitative analysis of LG/isoLG adducts that incorporate the amino group of phosphatidylethanolamines (PEs) into LG/isoLGhydroxylactams. Notably, LC-MS/MS detection of these hydroxylactams is achieved with samples that are an order of magnitude smaller and sample processing is mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 55 publications
0
52
0
Order By: Relevance
“…Within this general background, the pro-fibrogenic features of IsoLGs are largely unknown although the formation of IsoLGs has been demonstrated by the detection of their adducts in several animal models of liver disease [16,28,29,50]. This paucity of information is largely consequent to the difficulty of precisely assessing the in vivo levels of IsoLG in physiological and pathological conditions, and to the fact that they do not exist in free form due to their extreme rapidity of adduction [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within this general background, the pro-fibrogenic features of IsoLGs are largely unknown although the formation of IsoLGs has been demonstrated by the detection of their adducts in several animal models of liver disease [16,28,29,50]. This paucity of information is largely consequent to the difficulty of precisely assessing the in vivo levels of IsoLG in physiological and pathological conditions, and to the fact that they do not exist in free form due to their extreme rapidity of adduction [16].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the concentration of IsoLG-phosphatidylethanolamine (IsoLG-PE) adducts in whole livers of ethanol-fed mice was shown to be approximately 30 nM [28]. In addition, previous experimental evidence obtained in in vitro studies has suggested that IsoLG-PE may have a limited incorporation into the cells leading to the need of employing higher doses in order to elicit biological effects [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the formation of a family of al-PEs including IsoLG-PE has been recently established ( 11,18 ), the mechanism by which these compounds are metabolized has been unknown. Our studies demonstrate that cells utilize NAPE-PLD to rapidly degrade IsoLG-PE to IsoLG-Etn, which then undergoes further metabolism ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…IsoLGs have been shown to posttranslationally modify free primary amino groups present in biomolecules with an avidity greatly exceeding other reactive oxidized lipids ( 26,27 ). Targets of isoLG modifi cation include proteins and phospholipids (PLs) in the serum, the vasculature, and the eye, forming stable covalent adducts with isoLGs (26)(27)(28)(29). IsoLG adduct levels have been shown to be a biomarker of oxidative stress, increased in patients with atherosclerosis, renal disease, and AMD ( 28,30,31 ).…”
Section: Measurement Of Catalytic Activitymentioning
confidence: 99%